2014
DOI: 10.1177/0954008314553041
|View full text |Cite
|
Sign up to set email alerts
|

Influences of organic montmorillonite on the combustion behaviors and thermal stability of polyamide 6/polystyrene blends

Abstract: The nanocomposites of polyamide 6/polystyrene (PA6/PS) with different contents of organic montmorillonite (OMMT) have been obtained by melt blending. The combustion behaviors, morphology of char residues, and thermal stability of nanocomposites have been characterized by cone calorimeter tests (CCT), electron probe microanalysis, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The CCT results indicated that the OMMT was an efficient flame retardant (FR) in the FR-PA6/PS blends. The he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The nanoclay-produced silicates char on the surface layer of HDPE/BF blends increased the flame resistance of the samples. This was consistent with previous studies [25,27]. The tortuous path provided by the silicate layers had better barrier property to the oxygen and heat which delayed the burning capacity of the composite [19,30].…”
Section: Fire Behaviorsupporting
confidence: 82%
See 2 more Smart Citations
“…The nanoclay-produced silicates char on the surface layer of HDPE/BF blends increased the flame resistance of the samples. This was consistent with previous studies [25,27]. The tortuous path provided by the silicate layers had better barrier property to the oxygen and heat which delayed the burning capacity of the composite [19,30].…”
Section: Fire Behaviorsupporting
confidence: 82%
“…It was found that the addition of clay slightly improved the onset of the degradation of the composites. The increase of thermal stability was attributed to the hindered diffusion of volatile decomposition products by the clay particles in the polymer matrix [25][26][27]. The most likely explanation is that the well dispersed individual layers of intercalated/exfoliated clay platelets form torturous path, which inhibit the passage of volatile degradation product from the polymer matrix [28].…”
Section: Tga Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, polymer layered silicate nanocomposites have attracted attention in many fields, e.g., in industry exploitation and fundamental research 1,2 . These materials exhibit excellent mechanical and thermal properties, decrease in gas/vapor permeability, and reduced flammability in the presence of a small amount of the silicate, as compared with the polymer itself [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide 6 (PA6)/polystyrene (PS) blends are of considerable research interest because they have good commercial potential and they are expected to have combined advantages of PA6 that is strong, tough, abrasion‐, corrosion‐, and heat‐resistant, and PS that is stiff, low moisture sorption, low cost, and easy‐processing . Similar to other types of immiscible polymer blends processed under typical extrusion conditions, the size of the dispersed phase is usually large, in micrometer range, and much effort has been devoted to reduce the size of the dispersed phase by adding a compatibilizer such as maleic anhydride‐grafted PS and poly(styrene‐ g ‐ethylene oxide) .…”
Section: Introductionmentioning
confidence: 99%